Effect of the factors affecting high-performance p-aramid fibre dyeing and their optimization. Issue 2 (30th July 2020) - Iqbal, Kashif; Azam, Farooq; Safdar, Faiza; Ashraf, Munir; Rehman, Abdur; Ullah, Tehseen
Abstract : Purpose: This study aims to evaluate the dyeing of the p-aramid fibre with cationic dyes and investigate the effect of dyeing in the protection of the fibre from ultraviolet (UV) light. Design/methodology/approach: P-aramid fabric has been dyed with cationic dyes using benzyl alcohol as swelling agent to promote the penetration of dye molecules into the fibre. The fabrics were evaluated against colour strength (K/S) value and colour fastness properties after dyed with cationic dyes using full factorial design. This design was used to study the effect of factors that affect the response variables as well as to study the interactions among the factors on response variable. The bursting strength, scanning electron microscopy analysis and X-ray diffraction analysis of undyed and dyed p-aramid fabric were performed before and after exposure to UV light to investigate the changes in mechanical behaviour. Findings: The results show that the p-aramid fabric dyed with cationic dyes has good K/S values and good fastness properties. The exposure of undyed p-aramid fabric to UV light causes serious loss in strength over short duration i.e. 40 h. Dyeing of p-aramid fabric enhances the resistance to UV light which reduces the loss in strength. Originality/value: Most of the work is patented and no one has done the process optimization for the industry, so this study offers promising outcomes concerning the dyeing of p-aramid fabric with enhanced shade depth and good colour fastness characteristics.